2015
DOI: 10.1016/j.drugalcdep.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Abuse liability of the dietary supplement dimethylamylamine

Abstract: Background Dimethylamylamine (DMAA) is a component of many dietary supplements and has recently been associated with numerous adverse effects, prompting the US military and World Anti-Doping Agency to ban its use as a supplement. The current study aimed to elucidate the abuse liability profile of DMAA. Methods Dose-response studies of DMAA were performed with Swiss-Webster mice in locomotor and conditioned place-preference assays. The discriminative stimulus effects of DMAA were investigated in Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
(33 reference statements)
2
21
0
1
Order By: Relevance
“…We note that studies have observed DMAA's long half-life, with repeated doses within 24-36 h and dosages of greater than 100-200 mg increasing risk of adverse effects (Venhuis & de Kaste, 2012). Abuse liability of DMAA is reported to be similar to stimulants such as cocaine and methamphetamine (Dolan & Gatch, 2015). Adverse sympathomimetic symptoms reported by these users are similar to those described by Gee et al (2010Gee et al ( , 2012 in New Zealand, and deterred follow-up or chronic use.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We note that studies have observed DMAA's long half-life, with repeated doses within 24-36 h and dosages of greater than 100-200 mg increasing risk of adverse effects (Venhuis & de Kaste, 2012). Abuse liability of DMAA is reported to be similar to stimulants such as cocaine and methamphetamine (Dolan & Gatch, 2015). Adverse sympathomimetic symptoms reported by these users are similar to those described by Gee et al (2010Gee et al ( , 2012 in New Zealand, and deterred follow-up or chronic use.…”
Section: Discussionsupporting
confidence: 63%
“…The compound was originally patented by Eli Lilly for use as nasal decongestant (Venhuis & de Kaste, 2012). DMAA is banned by the US Food and Drug Administration (FDA) (Dolan & Gatch, 2015) and by World Anti-Doping Agency in their 2010 Prohibited list (listed under its synonym 'methylhexaneamine'). Emerging analogues on legislative controls have included '1,3-dimethylbutylamine' (DMBA) found in dietary supplements (Cohen, Travis, & Venhuis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, both compounds produced rapid onset locomotor depression at lower doses, and slower onset, long-lasting locomotor stimulation at higher doses. In addition, the cathinone flephedrone (Gatch et al, 2013), the sympathomimetic dimethylamylamine (Dolan & Gatch, 2015), and the phenethylamine hallucinogens 2C-D and DOC (Eshleman et al, 2014) produced a profile similar to that of MDAI and MDMA: depressant effects followed by rebound stimulant effects. In contrast, a wide range of psychostimulants produce locomotor stimulation, often in an-inverted U-shaped function, such that increasing doses produce increases in locomotor activity, with the highest doses producing marked decreases in locomotor activity (Carroll et al, 2009; Gatch et al, 2013; 2015a; 2015b; Katz, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Registered as geranamine the DMAA reappeared on the market in 2006 as an ingredient in various dietary supplements [10]. However, several adverse effects began to be associated with the use of products containing DMAA.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have already been performed in humans as described, only 1 study was performed in animal model and only 1 study in cell culture [6, 10], showing the lack of mechanistic studies. Also, studies showing that those supplements are safe and well tolerated were from groups sponsored by its manufacturer, the USP labs [1, 3, 17, 18].…”
Section: Introductionmentioning
confidence: 99%